From Migration to Dependency: Remittances, Family Economy, and the Need for Population Education in Rural Java - Khasyanah, Nila Trya Khasyanah; Susilo, Singgih; Lailatin, Sri; Choiri, Misbachul (CV Bumi Spasial, 2026)
The interest of residents of Tunggangri Village in becoming Indonesian Migrant Workers (PMI) is closely related to economic challenges, as working abroad is expected to provide higher income compared to domestic employment and to better support family finances. This study aims to identify the characteristics of Indonesian migrant workers in Tunggangri Village based on demographic, social, and economic aspects, as well as to examine the contribution of remittances to family income and their utilization by households in the area of origin. The research was conducted in Tunggangri Village, Kalidawir District, Tulungagung Regency, using a quantitative approach with a descriptive research design. Sample size was determined using the Slovin formula and proportional random sampling. Primary data were collected through observation, structured interviews, and documentation. From a total population of 177 active migrant workers, 123 respondents were selected as samples based on the Slovin method. The findings indicate that the majority of Indonesian Migrant Workers in Tunggangri Village are of productive age, with their highest educational attainment being senior high school or its equivalent, and the most common occupations include factory work and employment in the construction sector. Furthermore, the contribution of remittances to family income in Tunggangri Village is considerable, with an average contribution rate of 67%. For many households, remittances function as the main or even sole source of income, reflecting a high level of economic dependence on funds sent by Indonesian Migrant Workers.